Effect of short-term exposure to low concentration of tebuconazole: morphological, histometric and functional modifications in Danio rerio liver. Issue 1 (31st December 2022) - Macirella, R.; Curcio, V.; Ahmed, A. I. M.; Pellegrino, D.; Brunelli, E.
Abstract: Due to its high toxicity and bioaccumulation tendency, tebuconazole (TBZ) is one of the ten substances posing the highest risk of harmful effects in aquatic ecosystems. The liver, a key compartment for xenobiotics detoxification, is also the organ in which TBZ mainly accumulates in fish. Herein, we investigated for the first time the morpho-functional changes induced in zebrafish ( Danio rerio ) liver after a short-term exposure (48, 96, and 192 hours) to a low, environmentally relevant concentration of TBZ (5 µg/L) to disclose the early effects under a realistic exposure scenario. We revealed that pathological alterations with varying degrees of severity could be detected in all the examined samples. The injuries become intense and irreversible with increased exposure time involving both hepatocytes and vascular components based on the degree of tissue changes. The main morphological alterations were: parenchyma dyschromia, macrophages infiltration, congestion of blood vessels, and sinusoids. TBZ exposure also resulted in a significant decrease in glycogen contents and hepatocyte dimensions, and the modulation of superoxide dismutase, an early indicator of oxidative stress. We demonstrated that even a very low dose of TBZ affects hepatic morphology and function, disrupting liver homeostasis and physiology.